PENGARUH KOMITMEN ORGANISASI, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI HOTEL PASIFIK BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This research aims to influence organizational commitment, discipline and motivation to employee performance at Hotel Pacific Batam. This study uses the data questionnaire distributed to employees who work at the Pacific Hotel Batam, distributed questionnaires 125 respondents with levels ranging from managers to staff. This study uses the individual level of analysis. The object of research is the Pacific Batam hotel employee. This study used multiple linear regression tests stattistik which include validity, reliability, normality, and R-square test. Results from the study showed the coefficient of determination (adjusted R2) shows that the coefficient of determination (R2) has a value of 0.764 which means that the variable variable employee performance can be explained by the variable organizational commitment, discipline and motivation, of 76, 4.0%, while the remaining 23, 4% is influenced by factors that do not exist in this study